Cryopreservation of mesenchymal stem cells within macroporous matrices after sucrose pretreatment - Trufanova, Natalia; Rogulska, Olena; Semenchenko, Olga; Mishchenko, Oleksii; Petrenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2025)
Mesenchymal stromal/stem cells (MSCs) attract the attention of scientists and specialists in various fields of medicine due to their high immunomodulatory and regenerative potential, ability to multilineage differentiation. Effective storage technologies are essential for the implementation of MSCs into medical and laboratory practice. The article investigates the effect of pretreatment with sucrose on the viability, metabolic activity and differentiation potential of MSCs after cryopreservation in three-dimensional (3D) macroporous matrices. The results of the study showed that pretreatment with sucrose increased the efficiency of cell cryopreservation in collagen matrices by slow cooling in the presence of 10% DMSO and serum. The viability and metabolic activity of cells after cryopreservation in 3D matrices was significantly higher when treated with sucrose. It was also found that cells after cryopreservation retained the ability to proliferate and multilineage differentiation. The findings suggest that using sucrose for cell pretreatment is a promising approach to reduce cryodamage during their cryopreservation in 3D matrices and opens up new opportunities for increasing the efficiency of storage of tissue-engineered constructs. Probl Cryobiol Cryomed. 2025; 35(2):103–9